Spatial Modeling of Flood Affected Areas of Krukut River in Pela-Mampang Segment, South Jakarta, Indonesia - Rakuasa, Heinrich; Sugandhi, Nadhi; Kusratmoko, Supriatna, Eko (Future Science / FSH-PH Publications, 2023)
Flooding is one of the most common natural disasters in Indonesia, and the capital city of DKI Jakarta is no exception. Every year, there are always areas that experience flooding, mainly triggered by the overflow of flowing rivers. Jakarta itself is located in a downstream area consisting of swampy areas that are floodplains. One of the river basins that most often experiences flooding is the Krukut River. This is mainly triggered by the high value of rainfall which can reach more than 200 mm in a day. Massive development along the riverbanks has exacerbated the flooding, especially in the Pela Mampang segment which includes Pela Mampang Village, Mampang Prapatan Subdistrict and Petogogan Village, Kebayoran Baru Subdistrict. This research models two-dimensional flood inundation using the HEC-RAS program to describe the distribution of potential floods for return periods of 2, 5, 10, 25, 50 and 100 years. In addition, a spatial analysis of the affected infrastructure up to the RT level was also conducted to provide an overview of the extent of inundation using 4 types of classifications (low, medium, high and extreme). The results showed that 19 out of 150 RTs in Pela Mampang urban village and 33 out of 79 RTs in Petogogan urban village were flooded with a total inundation area of 100-year flood reaching 39.58 ha. The affected infrastructure reached 1,903 units with the area of inundated roads reaching 3.27 ha. It is hoped that this research can provide input for future infrastructure planning and river management in order to anticipate and mitigate disasters better.